Groundwater Conservation with Hole Infiltration of Biopore Cube. (August 2019) - Syahruddin, Muhammad Hamzah; Amiruddin,; Halide, Halmar; Sakka,; Makhrani,
Abstract: Analysis of groundwater conservation with cube biopore infiltration holes using the value of soil permeability, the amount of rainfall, and the depth of the groundwater level. The groundwater conservation research method is carried out by making the cavity biopore infiltration holes to absorb the volume of rainwater and domestic waste water into the soil. Conservation is suitable for homes that have enough yard. The main reason is to use cube infiltration holes to accommodate large and small organic waste. Organic waste is trees, grass and domestic waste. For a small house yard, conservation of ground water enough with a cylindrical hole diameter of 10 cm. Benefits of biopore infiltration holes are reducing surface runoff, producing manure, fertilizing soil, reducing waste piles, and conserving ground water. The research objective was to analyze the cube biopore infiltration holes based on soil permeability, rainfall intensity, depth of groundwater level, and volume of organic waste. The results of the analysis can be obtained from the cube biopore infiltration holes which can absorb all the rainwater which can accommodate all organic waste. The results of permeability testing show that the average soil permeability is 0.00112 cm/s and the yield of maximum discharge runoff water in January is 97.57 cm3/second. The ground water level is two meters. While the volume of organic waste is one cubic per month. The result of the analysis showed that the area of cake absorption was 8.73 m2. When converted to a cube absorption field it takes approximately 8 meters wide by 0.5 meters and a depth of 0.5 meters. When divided into four cavity recharge holes LRB1 obtained area of 4 m2, LRB2 area of 2.7 m2, LRB3 area 2 m2, and LRB4 as reserve.